Mozart's Symphonies: Context, Performance Practice, Reception - Zaslaw, Neal -1939 (Oxford Clarendon New York Oxford University Press, 1989)
Published to coincide with the bicentennial of Mozart's death, this book identifies and evaluates every symphony that has ever been associated with the name of Wolfgang Amadeus Mozart, nearly 100 in all. Zaslaw, who served as the musicological supervisor for the complete recordings of Mozart's symphonies by Jaap Schröder, Christopher Hogwood, and the Academy of Ancient Music, draws on exhaustive research and his own experience in presenting this comprehensive study. He places each symphony in its musical and cultural context, explores the role each played in Mozart's creative life, and reveals what is known about how Mozart's symphonies, and those of his contemporaries, were performed. In doing so, he has created an invaluable contribution to Mozart scholarship that will long stand as the definitive treatment of its subject.
Includes bibliographical references (p. [569]-600).
Keywords: Mozart, Wolfgang Amadeus -- 1756-1791; Hogwood, Christopher -- 1941-2014; Schröder, Jaap -- 1925-2020; Academy of Ancient Music (London, United Kingdom); 18th Century (1701-1800); Symphony; Historically informed performance; Musical analysis; Legacy; Austria